Al-Tememe transform in solving developed missile automatic control problem - Kuffi, Emad; Sabah Abbas, Elaf; Obeid Mebayet, Salman (International Journal of Engineering and Technology, 2019)
Al-Tememe transform is a new transform that is recently emerged, as a result to its modernity, it has not exploited properly in many applications. Missile automatic control problem is an application of the second order ordinary differential equation with constant coefficients, for that reason many methods in solving second order ordinary differential equations had been used in solving that problem, however, Al-Tememe transform had never been used in solving the problem of missile automatic control. In this paper Al-Tememe transform has been used to solve the developed problem of missile automatic control, which is an application of the second order ordinary differential equations with variable coefficients.Â